Pengaruh Firm Generated Content, Electronic Word of Mouth, Celebrity Endorsement, Harga dan Fasilitas terhadap Keputusan Memilih Klinik Gigi - Putri, Vania Mariska; Sijabat, Rosdiana (Jurnal InterAct, 2021)
With the development and increasing number of dental clinics, customers are exposed to more options when it comes to choosing dental clinic. Therefore, social media marketing strategies are becoming more popular among dental services. This study aims to determine the effect of firm generated content, electronic word of mouth, celebrity endorsement, price, and facilities towards customer’s purchase decision in choosing dental clinic. This research is a case study of Dentalosophy Dental Clinic which involved 100 respondents who had done dental treatments in Dentalosophy during January to December 2020. Data collection was conducted by distributing questionnaires using purposive non-probability sampling method. Furthermore, the data were analyzed using descriptive statistical analysis and multiple linear regression methods. The study shows that firm generated content, electronic word of mouth, celebrity endorsement, and facilities have positive and significant effect towards customer’s purchase decision in choosing dental clinic. Contrastingly, price does not have a negative and insignificant effect on customer’s decision in choosing dental clinic. Based on the result, Dentalosophy shall do further analysis, planning and evaluation of marketing strategies related to firm generated content, electronic word of mouth, and celebrity endorsement. Dentalosophy should also be able to maintain and improve their facilities as well as providing qualified health protocol especially during COVID-19 pandemic. Further study is expected to analyze the effect of other variables such as location, and dentist’s reputation towards purchase decision in choosing dental clinic.